2015
DOI: 10.1590/0103-9016-2014-0221
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical aspects of wheat resistance to leaf blast mediated by silicon

Abstract: Blast, caused by Pyricularia oryzae, has become a significant disease threat to wheat (Triticum aestivum L.) in Brazil. This study aimed to investigate at the histochemical level if silicon (Si) could enhance the production of flavonoids in the leaves of wheat plants in response to P. oryzae infection. Plants from the Aliança cultivar, which are susceptible to blast, were grown in hydroponic cultures containing 0 (-Si) or 2 mM of Si (+Si) and inoculated by spraying a conidial suspension of P. oryzae (1 × 10 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
3
31
0
2
Order By: Relevance
“…They also observed that expression of all defence related genes was significantly increased on infection but expression level was two to three times higher for +Si plants as compared to -Si counterparts. Similar results of increased Si concentration causing reduced fungal growth were reported by Silva et al (2015). They found that at histochemical level, Si is involved in the potentiation of the biosynthetic pathway of flavonoids that increases wheat resistance to blast.…”
Section: Resistance Mechanismsupporting
confidence: 83%
See 1 more Smart Citation
“…They also observed that expression of all defence related genes was significantly increased on infection but expression level was two to three times higher for +Si plants as compared to -Si counterparts. Similar results of increased Si concentration causing reduced fungal growth were reported by Silva et al (2015). They found that at histochemical level, Si is involved in the potentiation of the biosynthetic pathway of flavonoids that increases wheat resistance to blast.…”
Section: Resistance Mechanismsupporting
confidence: 83%
“…Ever since its first report, blast pathogen was variously named by researchers for example, Pyricularia oryzae Oliveira et al, 2015;Cruz et al, 2015a;Silva et al, 2015), Pyricularia grisea (Filha et al, 2011;Kohli et al, 2011;Rocha et al, 2014), Magnaporthe grisea (Urashima and Kato, 1994;Peng et al, 2011;Pagani et al, 2014) and M. oryzae Triticum (Cruz et al, 2015a). Blast pathogen has shown capability to evolve fast to adapt to new climates.…”
Section: Pathogen Disease Development and Host Variationmentioning
confidence: 99%
“…; Silva et al. ). Leaf sections from non‐inoculated plants for both cultivars were also collected and preserved to serve as the control treatment.…”
Section: Methodsmentioning
confidence: 99%
“…() and Silva et al. () with a few modifications. Briefly, approximately 30–40 transverse sections (10–30 μ m thick) per petiole and leaf samples were obtained from non‐inoculated and infected leaf sections from plants of each cultivar using a table microtome (model LPC; Rolemberg and Bhering Commercial and Importation LTDA, Belo Horizonte, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation